Selected Lectures of the Congress of Pediatrics; Cagliari (Italy); October 25, 2024 - - (Hygeia Press di Corridori Marinella, 2024)
Selected Lectures of the Congress of Pediatrics; Cagliari (Italy); October 25, 2024   The Congress of Pediatrics is a Satellite Meeting of the 20th International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 23rd-26th, 2024.   LECT 1. TH2 INFLAMMATION AND INBORN ERRORS OF IMMUNITY (IEI): AN EVER-EXPANDING UNIVERSE. FOCUS ON STAT6 GAIN-OF-FUNCTION MUTATIONS • I. Taietti, R. Castagnoli, A. Licari, G.L. Marseglia (Pavia, Italy) LECT 2. ANTIBIOTICS AND PROBIOTICS: WHEN TO USE THEM TOGETHER IN PEDIATRICS • S. Esposito (Parma, Italy) LECT 3. THE LONG-TERM FOLLOW-UP OF PRETERM INFANTS • M. Agosti (Varese, Italy) LECT 4. LOW DOSE MEDICINE AND RECURRENT RESPIRATORY INFECTIONS: A DELPHI CONSENSUS SURVEY • G. Bona, M. Agosti, A. Arrighi, S. Bernasconi, G. Ciprandi, S. Leonardi, G.L. Marseglia (Novara, Varese, Arezzo, Genoa, Catania, and Pavia, Italy) LECT 5. RATIONAL USE OF NUTRACEUTICALS IN PEDIATRICS • G. Trapani (Sanremo, Italy) LECT 6. THE PAST, THE PRESENT: WHAT FUTURE FOR PEDIATRICS AND PEDIATRIC SOCIETIES? • S. Vendemmia, I. Pezone, D. Perri, V. Ferrara, M. Vendemmia (Aversa, Rome and Naples, Italy) LECT 7. THE FAMILY PEDIATRICIAN AND THE FUTURE • A. D'Avino (Naples, Italy) LECT 8. ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD): NEWS AND UPDATES • M. Carotenuto (Caserta, Italy) LECT 9. FEVER IN PEDIATRIC PATIENTS: AN EAR-NOSE-THROAT (ENT) PERSPECTIVE • A. Varricchio, F.P. Brunese, A. Varricchio (Campobasso, Caserta and Milan, Italy) LECT 10. THROMBOCYTOPENIA IN CHILDREN • S. Barella (Cagliari, Italy) LECT 11. EXPOSURE TO DIGITAL DEVICES IN CHILDHOOD: A STUDY OF 1,332 CHILDREN AND PREADOLESCENTS • L. Pisano, O. Al Jamal (Cagliari, Italy) LECT 12. PRESENTATION OF THE BOOK "PEDIATRIC ELECTROCARDIOGRAPHY - A SIMPLIFIED APPROACH" • F. De Luca (Catania, Italy) LECT 13. PRESENTATION OF THE BOOK "NUTRACEUTICALS IN CLINICAL PRACTICE: SUPPLEMENTATION AND PREVENTION, A REASONED APPROACH TO HEALTH AND WELLNESS" • G. Trapani (Sanremo, Italy) LECT 14. PRIMARY HYPEROXALURIA TYPE 1 • V. Manca, G. Masnata (Cagliari, Italy) LECT 15. HEREDITARY HOMOZYGOUS FAMILIAL HYPERCHOLESTEROLEMIA (HoFH) • S. Muntoni, C. Piras, L. Atzori (Cagliari, Italy) LECT 16. PROGRESSIVE FAMILIAL INTRAHEPATIC CHOLESTASIS • A. Pietrobattista (Rome, Italy) LECT 17. ALFA MANNOSIDOSIS: A CHALLENGING DIAGNOSIS FOR A TREATABLE DISEASE • M. Balzarini, F. Zanco, C. Sbaffi (Cagliari, Italy) LECT 18. LYSOSOMAL ACID LIPASE (LAL) DEFICIENCY: CLINICAL SPECTRUM, DIFFERENTIAL DIAGNOSIS AND SPECIFIC THERAPY • V. Casotti (Bergamo, Italy) LECT 19. AROMATIC L-AMINO ACID DECARBOXYLASE (AADC) DEFICIENCY • T. Foiadelli (Pavia, Italy) LECT 20. ROLE OF ALKALINE PHOSPHATASE IN THE DIAGNOSIS OF HYPOPHOSHATASIA • S. Savasta (Cagliari, Italy) LECT 21. DONKEY MILK BETWEEN PAST AND FUTURE • V. Fanos, M. Corridori (Cagliari and Quartu Sant'Elena, Italy) LECT 22. THE QUALITY OF DONKEY MILK • M. Martini (Pisa, Italy) LECT 23. DONKEY MILK: A RESOURCE IN PRETERM INFANTS NUTRITION • E. Bertino, G. Maiocco, L. Cavallarin, M. Giribaldi, S. Deantoni, C. Peila, A. Coscia (Turin and Grugliasco, Italy) LECT 24. METABOLOMICS OF DONKEY MILK • F. Cesare Marincola, V. Fanos (Cagliari, Italy) LECT 25. THE VIRTUAL KIDNAPPING OF YOUTH BY SOCIAL MEDIA • M. Leiner (El Paso, Texas, USA)